Kilka uwag o statusie onomastycznym odapelatywnych nazw osobowych w antroponimii rosyjskiej XVI wieku - Osmańska, Monika (Studia Rossica Posnaniensia, 2010)
The article is devoted to the personal names derived from the appellatives, particularly to the question of their belonging to the anthroponymical categories of “name” and “nickname”. Special attention has been given to the issue of presence and functioning of so called intrafamilial names in the old Russian anthroponimical system after the embracement of Christianity. The author attempts to formulate the criteria which would allow to distinguish between names and nicknames and presents the results of the analysis of 2096 separate anthropolexemes drawn from 16th century clerical texts.